Pengembangan Modul Pembelajaran Berbasis Masalah pada Mata Pelajaran Produk Kreatif dan Kewirausahaan (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to develop a feasible and effective problem-based learning module. This research is a type of research and development with the stages of preliminary research, model development, and model testing. The number of samples in this study consisted of 10 teachers of Creative Products and Entrepreneurship (PKK), one material expert, one media expert, and 182 students. The instruments used are interview guides, questionnaires, and pretest and post-test questions. The data analysis technique in this study used a qualitative and quantitative approach. The results show that the learning model for PKK subjects used in Vocational High Schools is quite varied; learning activities use learning models oriented to student activities. However, teachers still experience several obstacles, such as teaching materials or textbooks that are still limited to support active learning activities, so it is necessary to develop problem-based learning module (PBL). The results of the module assessment carried out by experts, vocational teachers, and students were categorized as "feasible." Testing the module by acquiring an average N-Gain score for pretest and post-test shows that the problem-based module is quite effective in use with an effective contribution in the "strong effect" category